Centro de capacitación de grupos indígenas “EL POIRA” (2020)
Indigenous groups are part of the territory and the history of the region, the culture that each reservation represents is a subject of interest since they are part of the Tolimense heritage, but which, in turn, have been little forgotten. excluding them, where they are not provided with adequate care that favors their way and quality of life. Choosing unsuitable ways to survive day after day. According to the search for information given in the project, it is proposed to develop an architectural proposal to serve a certain number of indigenous population in the city of Ibagué, a training center which aims to provide favorable services for their training and job growth and to improve their living conditions. Along with an urban intervention that allows improving the conditions of the San Pedro Alejandrino neighborhood, reinforcing the security and lighting of the sector accompanied by a recovery of the infrastructure of the road network, in order to offer benefits to the indigenous population that is based in The city of Ibagué. For the execution of the project, 3 methodological phases were continued, involving the analysis of the sector, field work, the search for documents that complement the proposal. In order to achieve positive problems that strengthen indigenous groups, through the design of multifunctional training equipment.